RETRACTED ARTICLE: Long non-coding RNA 91H regulates IGF2 expression by interacting with IGF2BP2 and promotes tumorigenesis in colorectal cancer - Tianyi Gao; Xiangxiang Liu; Bangshun He; Yuqin Pan; Shukui Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Tianyi Gao, Xiangxiang Liu, Bangshun He, Yuqin Pan & Shukui Wang (2020) Long non-coding RNA 91H regulates IGF2 expression by interacting with IGF2BP2 and promotes tumorigenesis in colorectal cancer, Artificial Cells, Nanomedicine, and Biotechnology, 48:1, 664-671, DOI: 10.1080/21691401.2020.1727491Since publication, the authors noticed duplication in Figure 1A and 4A. As this error directly impacts the reported results and conclusions the authors alerted the issue to the Editor and Publisher to request correction. The authors acknowledged that they had made mistakes and the Editor and Publisher found there to be fundamental flaws present within the requested corrections, as well as the rest of the paper. The authors have agreed to the retraction of this article.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.